Shift work and the risk of knee osteoarthritis among Chinese workers: a retrospective cohort study - Zhou, Mingqing; Yang, Shijie; Guo, Yanjun; Wang, Dongming; Qiu, Weihong; Wang, Bin; Mu, Ge; Cao, Limin; Zhang, Zhuang; Chen, Wenqian (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVES ': 'Shift work is associated with metabolic disorders as it disturbs circadian rhythms. However, the potential association of shift work with knee osteoarthritis (KOA), a metabolic-related disease, has not been confirmed. The objective of this study was to quantify the association of shift work with the risk of KOA. ' ' METHODS ': 'This retrospective cohort study comprising 13 741 retired workers from the Dongfeng Motor Corporation. KOA was defined by knee pain and clinical X-ray radiographs. Occupational history, including job description and shift work, was collected from face-to-face interviews using questionnaires. Cox proportional hazards regression models were used to estimate exposure–response relationships. ' ' RESULTS ': 'During the 590 085 person-years of follow-up, a total of 847 cases of KOA (incidence of KOA was 143.5 per 100 000 person-years) were identified. After adjusting for potential confounders, shift work was independently associated with an elevated risk of KOA [hazard ratio (HR) 1.19, 95% confidence interval 1.03–1.36]. Compared with daytime workers, the risk of KOA increased with prolonged periods of shift work; the HR of KOA for participants with 1–9 years, 10–19 years, and ≥20 years shift work were 1.03 (95% CI 0.84–1.26), 1.19 (95% CI 0.98–1.46), and 1.42 (95% CI 1.15–1.76), respectively. The HR for KOA associated with shift work gradually decreased as the period after finishing shift work increased. ' ' CONCLUSION ': 'Our results indicated that shift work could be an independent risk factor for KOA.
Keywords: China; Chinese worker; circadian rhythm; cohort study; knee osteoarthritis; metabolic disorder; occupational health; retrospective cohort study; shift rotation; shift work; shift worker; worker